"A study of change of posture on the pulmonary function tests : can it help copd patients ?" - Saxena, Jalaj; Gupta, Sushma; Saxena, Sonali (Indian Journal of Community Health, 2006)
Objectives : To know the pulmonary function tests in sitting, supine and standing postures in North Indian population Is there any change in PFTs due to change in posture Settings: Department of Physiology, G.S.V.M. Medical College, Kanpur and Escorts Heart Centre, Kanpur Participants : 50 male and 30 female healthy, non-smoker volunteers comprising of 50 students of first year MBBS and 30 volunteers at Escorts Heart Centre, Kanpur Measurements : PFTs, FEV1, FVC, FER, PEFR and TV Statistical analysis : Students't' test Results: The FEV1, FVC and PEFR increased significantly from supine to sitting to standing posture in both males and females. The FER significantly increased only when moving from supine to sitting in both males and females. The TV increased significantly by moving from supine to sitting and also from supine to standing postures in both males and females.